Light-induced gold-catalyzed Hiyama arylation: a coupling access to biarylboronates - Xie, Jin; Sekine, Kohei; Witzel, Sina; Krämer, Petra; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Angewandte Chemie. International edition, 2018)
Organoboron compounds are versatile synthetic building blocks. We herein report a new strategy, a photochemical gold-catalyzed chemo-selective Hiyama arylation of B,Si bifunctionalized reagents with diazonium salts, which is orthogonal to common strategies and therefore a unique tool for synthesis of valuable biarylboronates. With this new methodology a wide array of diversely functionalized sp2- and sp3-hybridized biarylboronates were obtained. Notably, the synergism of gold catalysis with copper catalysis or palladium catalysis, allows for one-pot iterative C−X (heteroatom) and C−C couplings for the rapid assembly of several simple fragments to relatively complex molecules. Mechanistic studies indicated that photosensitizer-free conditions were superior to gold/Ru(bpy)3Cl2 dual catalysis.